Differences in Psychosocial Factors and Experimental Pain Sensitivity Between Hispanics and Non-Hispanic Whites from the U.S.-Mexico Border. Issue 11 (4th March 2021) - Valencia, Carolina; Smiley, Aaron; Giron, Megan; Stacy, Johnathan; Rodriguez, Isaac; Umucu, Emre
Abstract: Purpose: Research suggests that ethnicity is a predictor of pain-related outcomes; however, studies comparing the differences in experimental pain sensitivity between Hispanics and non-Hispanic Whites (NHW) are scarce. This study investigated these differences between Hispanics and NHW from the U.S.- Mexico border. Methods: Fifty-eight healthy participants completed the survey packet, which included a demographic and a psychosocial factors questionnaire. Participants underwent quantitative sensory testing, which included heat pain threshold, heat pain tolerance, Suprathreshold Heat Pain Response (SHPR), and Conditioned Pain Modulation (CPM). SHPR was induced by repeated thermal stimuli in both thenar eminences. CPM was assessed using SHPR as the experimental stimulus and cold pressor task as the conditioning stimulus. Results: Analyses showed significant differences in experimental pain measures believed to be representative of facilitatory pain processing including SHPR and heat pain threshold, where Hispanics reported significantly higher pain ratings than NHW. Hispanics also reported higher levels of ethnic identity and acculturation. However, these factors were not significantly associated with experimental pain sensitivity. Conclusion: The experimental pain sensitivity and psychosocial factors included in this study differed by ethnic group, where Hispanics reported significantly higher pain ratings, when compared with NHW. However, ethnic identity and acculturation were not associated with these pain-related outcomes. Overall, enhanced understanding by clinicians of pain sensitivity and disparities in the pain experience between ethnic groups allows for increased cultural sensitivity and can be used to optimize pain treatment on an individual-by-individual basis.